Analysis Financial Distress Potential in Asean Industrial Companies Using Altman Z-Score and Springate Methods - Resmi Yunisa; Fitri Santi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the potential for financial distress in the industrial sector companies across five ASEAN countries, using the Altman Z-score (1993) and Springate (1978) methods. Subsequently, these estimations are utilized to determine the error rate in classifying companies into specific groups, such as failed, safe, and grey-area companies. To measure the significance of differences among these groups, an independent sample t-test is employed. The bankruptcy analysis results from the Altman Z-Score and Springate methods within the industrial sector companies across ASEAN countries (Indonesia, Malaysia, Philippines, Singapore, and Thailand) in 2018 until 2020 indicate varying levels of financial distress.